Trigonometry Addiction

Geometry Level 3

( 1 + tan 7 ) ( 1 + tan 1 7 ) ( 1 + tan 2 8 ) ( 1 + tan 3 8 ) = ? \large (1+\tan7^\circ)(1+\tan17^\circ)(1+\tan28^\circ)(1+\tan38^\circ) = \, ?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Dec 25, 2015

( 1 + tan 7 ) ( 1 + tan 1 7 ) ( 1 + tan 2 8 ) ( 1 + tan 3 8 ) = ( 1 + tan 7 ) ( 1 + tan 3 8 ) ( 1 + tan 1 7 ) ( 1 + tan 2 8 ) = ( 1 + tan 7 + tan 3 8 + tan 7 tan 3 8 ) ( 1 + tan 1 7 + tan 2 8 + tan 1 7 tan 2 8 ) = ( 1 + tan 7 tan 3 8 + ( 1 tan 7 tan 3 8 ) × tan 7 + tan 3 8 1 tan 7 tan 3 8 ) × ( 1 + tan 1 7 tan 2 8 + ( 1 tan 1 7 tan 2 8 ) × tan 1 7 + tan 2 8 1 tan 1 7 tan 2 8 ) = ( 1 + tan 7 tan 3 8 + ( 1 tan 7 tan 3 8 ) tan 4 5 ) ( 1 + tan 1 7 tan 2 8 + ( 1 tan 1 7 tan 2 8 ) tan 4 5 ) = ( 1 + tan 7 tan 3 8 + 1 tan 7 tan 3 8 ) ( 1 + tan 1 7 tan 2 8 + 1 tan 1 7 tan 2 8 ) = ( 1 + 1 ) ( 1 + 1 ) = 4 (1+\tan 7^\circ)(1+\tan 17^\circ)(1+\tan 28^\circ)(1+\tan 38^\circ) \\ = (1+\tan 7^\circ)(1+\tan 38^\circ)(1+\tan 17^\circ)(1+\tan 28^\circ) \\ = (1+\tan 7^\circ +\tan 38^\circ +\tan 7^\circ \tan 38^\circ)(1+\tan 17^\circ +\tan 28^\circ +\tan 17^\circ \tan 28^\circ) \\ = \left(1+\tan 7^\circ \tan 38^\circ+(1-\tan 7^\circ \tan 38^\circ) \times \dfrac{\tan 7^\circ +\tan 38^\circ}{1-\tan 7^\circ \tan 38^\circ}\right) \\ \quad \times \left(1+\tan 17^\circ \tan 28^\circ+(1-\tan 17^\circ \tan 28^\circ) \times \dfrac{\tan 17^\circ +\tan 28^\circ}{1-\tan 17^\circ \tan 28^\circ}\right) \\ = \left(1+\tan 7^\circ \tan 38^\circ+(1-\tan 7^\circ \tan 38^\circ) \tan 45^\circ \right) \left(1+\tan 17^\circ \tan 28^\circ+(1-\tan 17^\circ \tan 28^\circ)\tan 45^\circ \right) \\ = \left(1+\tan 7^\circ \tan 38^\circ+1-\tan 7^\circ \tan 38^\circ \right) \left(1+\tan 17^\circ \tan 28^\circ+1-\tan 17^\circ \tan 28^\circ \right) \\ = (1+1)(1+1) = \boxed{4}

Rohit Ner
Dec 24, 2015

( 1 + tan A ) ( 1 + tan B ) = 2 ; A + B = π 4 (1+\tan A)(1+\tan B)=2 ; A+B=\frac{\pi}{4} .
So the answer turns out to be 4 \color{#3D99F6}{\boxed{4}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...